Functional tic-like behaviours during the COVID-19 pandemic: Follow-up over 12 months - Prato, Adriana; Saia, Federica; Milana, Maria Chiara; Scerbo, Miriam; Barone, Rita; Rizzo, Renata (Frontiers in Pediatrics, 2023)
- Background: Functional tics are included in the wide spectrum of functional movement disorders (FMDs). Their distinction from organic tics is challenging because they both phenomenologically present common features. During the COVID-19 pandemic, there has been an increase in functional tic-like behaviours in vulnerable children and adolescents after social media exposure. This study explores the phenomenology and course of a cohort of newly diagnosed functional tic-like behaviors. - Methods: We analysed clinical data of 243 patients affected by tic disorders collected at outpatient Tourette Clinic, Child and Adolescent Neurology and Psychiatry Unit, Catania University. Among the clinical cohort with functional tic-like behaviors, we evaluated the clinical course of symptoms at follow-up visits after 6 months and 12 months. Results: Among the cohort of 243 patients referred for evaluation at our centre, 11 were diagnosed with functional tic–like behaviours. The majority of participants with functional tic–like behaviours were female with a mean age of 15 years old and presented an explosive symptom’s onset. At follow-up visit after 12 months, patients with functional tic-like behaviors showed a significant variation in the severity of tics and anxiety symptoms. Conversely, depressive, and obsessive-compulsive symptoms did not significantly differ during the follow-up. - Conclusions: Our data suggest that several characteristics in clinical course and their phenomenology can help clinicians to distinguish functional tic–like behaviours from organic tics. Our results also suggest a better outcome for tics and anxiety symptoms respect on other comorbidities. A prompt diagnosis and management not only of tics but also comorbidities are recommended, as generally conventional pharmacotherapy for tics does not have positive effects on these patients.